1995
DOI: 10.2466/pms.1995.81.1.231
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of an Instructor: Dress and Students' Characteristics

Abstract: This study examined the influence of a female instructor's clothing style on students' perceptions of an instructor's characteristics. Social perception provided the theoretical framework. Formality of clothing style, students' clothing interest, and students' gender were the independent variables. Perception of the instructor's characteristics was the dependent variable. A 25-item questionnaire was administered to 216 college students from three universities. Perceptions of the instructor's characteristics va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 12 publications
4
28
0
Order By: Relevance
“…However, if the students in this study are typical, there are some lessons that may be learned from this research. In general, the results of this study support the recommendation made Lukavsky et al [27] that teachers should strive for a moderate clothing style. Students pay more attention to clothing as a cue when the teacher's inherent value is not apparent.…”
Section: Evt and Teacher Clothingsupporting
confidence: 90%
See 2 more Smart Citations
“…However, if the students in this study are typical, there are some lessons that may be learned from this research. In general, the results of this study support the recommendation made Lukavsky et al [27] that teachers should strive for a moderate clothing style. Students pay more attention to clothing as a cue when the teacher's inherent value is not apparent.…”
Section: Evt and Teacher Clothingsupporting
confidence: 90%
“…Similarly, Davis [26] found that formality was negatively associated with friendliness, sympathy, clarity of communication, enthusiasm, and flexibility but positively associated with knowledge. A moderate clothing style is formal enough to command respect, yet not so formal as to discourage contact among college students [27,28].…”
Section: Instructor Clothing As Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study Lukavsky, Butler and Harden (1995) found significant differences in student perception of three teacher characteristics (approachability, flexibility, and respect) based on whether the instructor was formally or informally dressed. Findings of the study showed that the instructor who dressed informally was rated most approachable and flexible, but at the same time commanded the least amount of respect.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Within the limited research that has been done in teacher attire, most has focused on student initial perceptions of teacher character traits, or first impressions, by using doctored photographs and other such methods (Davis, Clarke, Frances, et al 1992;Morris, Gorham, Cohen, & Huffman, 1996;Lukavsky, Butler, & Harden, 1995;Butler, & Roesel, 1989). A majority of studies have found that the more formal business attire a teacher wears, the more positive responses they receive in respect and power, but conversely they also receive the least positive response for approachability (Davis, Clarke, Frances, et al 1992;Morris, Gorham, Cohen, & Huffman, 1996;Lukavsky, Butler, & Harden, 1995;Butler, & Roesel, 1989).…”
Section: Review Of Related Literaturementioning
confidence: 99%